Intention to use electric vehicles in Malaysia, a modification theory of acceptance study - Liu, Yongchuang (2023)
Electric vehicles (EVs) have been developed as an efficient solution for reducing automobile emissions. To ensure the effective integration of EVs into current transportation systems, it is imperative to comprehend the factors that influence consumers’ intentions to purchase them. This study aims to provide insights into these factors by focusing on Malaysia current and potential drivers’ intention to use EVs. A questionnaire survey was conducted in March 2023 among current and potential drivers in Malaysia, resulting in the acquisition of 400 valid survey responses. The findings indicate that Perceived Ease of Use (PEOU), Environmental Concerns (EC), and Pricing Strategy (PS) are significantly associated with the intention to use electric vehicles among both current and potential drivers in Malaysia. Moreover, the study revealed that Perceived Usefulness (PU) and Safety Concerns (SC) exerted negative influences on consumers’ intentions to purchase EVs. These findings can offer practical guidance for devising effective marketing strategies and serve as a valuable reference for EV stakeholders seeking to enhance the effectiveness of current policies related to EV adoption.